A study of real hypersurfaces in complex space forms with condition on the Jacobi operator / Ren Shiquan - Ren, Shiquan (2012)
In this thesis, we first review some basic concepts in Riemannian geometry and then give a detailed survey on real hypersurfaces in a non-flat complex space form. After this, some new results on characterizing real hypersurfaces in a non-flat complex space form in terms of R are presented. The main results are proved in the last two chapters. We give a characterization for ruled real hypersurfaces in a non-flat complex space form by the condition (rXR) = 0, for X 2